A Federação da Indústria do Estado do Rio Grande do Sul no contexto da abertura 1974-1984 - Moraes, Gilmar Ferreira de (2007)
This thesis has the objective of describing the participation of Federação da Indústria do Estado do Rio Grande do Sul (FIERGS) in the political-economic context of military aperture. Within this proposal the relations between the increasing economical dificulties, government politics and the FIERGS attitudes towards the redemocratization process, will be considered in this work. The period considered in this research has its beggining in 1974 on Geisel s government, when the regime adopts a distension politics along with a timidly liberating measure (slow, gradual and safe). In this occasion, the industrial group, who was tradicionally identified with the agreement on the government s political-economic choices, starts to give signs of opposition. From that point on it starts to unleash a change articulated in the conduct patterns of the FIERGS in order to maintain the Militar Regime. The period considered has its ende with the last days of Figueiredo s government, that culminated with the end of military regime in Brazil.